Penyuluhan Seks Sebagai Upaya Pencegahan Pelecehan Seksual di Sekolah Dasar - Sujoko Waluyo; Vivi Uvaira Hasibuan; Wiwik Lestari; Fitri Yani (Jurnal Pengabdian Pada Masyarakat METHABDI, 2025)
Research on the prevention of sexual harassment in elementary schools requires a holistic approach involving all parties. A total of 25 elementary school students participated in this activity. Through material delivery, group discussions, and role-playing, participants were provided with a comprehensive understanding of various forms of sexual harassment, their impacts, and preventive and response measures. Evaluation results showed a significant increase in participants' knowledge and attitudes. Quantitative data analysis indicated a significant disparity between participants' pre-test and post-test scores (W=17.5; p=0.003), with the average post-test score exceeding the pre-test score. This finding indicates that after participating in the activity, participants' understanding of sexual harassment issues significantly improved. Further analysis of each item in the questionnaire revealed that the most significant difference occurred in questions regarding the types of sexual harassment (W=8; P<0.001). These results indicate that before participating in the activity, most participants were unaware that some of the behaviors they experienced or witnessed constituted sexual harassment. The program emphasized the importance of clear policies and procedures, education and training for teachers, school personnel, and students, and parental participation in prevention initiatives. Furthermore, the event emphasized the importance of creating a safe and inclusive school climate, as well as ongoing monitoring and evaluation of existing policies and programs. Collaboration with third parties was also deemed necessary to provide additional resources and support. By implementing these measures, elementary schools are expected to provide a safe and supportive environment for all children, build a healthy learning environment, and encourage overall child development. The strong collaboration with SD Kartini made this activity a success, and it is hoped that it can serve as a model for similar activities in the future.